ISBA: an independent set-based algorithm for automated partial reconfiguration module generation - He, Ruining; Ma, Yuchun; Zhao, Kang; Bian, Jinian (2012 IEEE/ACM International Conference on Computer-Aided Design (ICCAD), 2012)
Dynamic Partial Reconfiguration (DPR) on FPGAs has attracted significant research interests in recent years since it provides benefits such as reduced area and flexible functionality. However, due to the lack of supporting synthesis tools in current DPR design flow, leveraging these benefits requires specific designer expertise with laborious manual design effort. Considering the complicated concurrency relations among functions, it is challenging to properly select Partial Reconfiguration Modules (PR Modules) and partition them into groups so that the hardware modules can be swapped in and out during the run time. What's more, the design of PR Modules also impacts reconfiguration latency and resource utilization greatly. In this paper, we formulate the PR Module generation problem into a standard Maximum-Weight Independent Set Problem (MWISP) so that the original manual exploration can be solved optimally and automatically. Our proposed algorithm not only supports various design constraints, but also has the ability to consider multiple objectives such as area and reconfiguration delay. Experimental results show that our approach can optimize resource utilization and reduce reconfiguration delay with good scalability. Especially, the implementation of the real design case shows that our approach can be embedded in the Xilinx's DPR design flow successfully and it can save around 70% reconfiguration latency overhead compared with the heuristic PR Module generation approaches.